Ioan Bolovan, Rudolf Gräf (coordonatori), O istorie a Banatului. Compendiu [A history of Banat. Compendium], Cluj-Napoca, Editura Școala Ardeleană, 2023, 682 p. - CIOBANU, Alexandra (Studia Universitatis Babeș-Bolyai Historia, 2025)
It seems that the most important works on the history of Banat tend, at least in recent years, to be published anywhere but in the Banat. Thus, two years before The Banat of Temesvar appeared in the USA, an equally important, but quite different work on Banat was published in Cluj-Napoca – namely, the collective volume O istorie a Banatului: compendiu, coordinated by historians Ioan Bolovan and Rudolf Gräf and published under the aegis of the Romanian Academy. The work, now in its second edition, is dedicated to historian Nicolae Bocșan and opens with a word of appreciation by Romanian Academy president Ioan-Aurel Pop, a preface signed by Dan Dubină, member of Romanian Academy, and a foreword by the coordinators of the volume. I said that it differs completely from Timothy Olin’s work, and it does. While the latter is focused on a century and a half of the region’s history and presents it through the focal point of colonization, O istorie a Banatului, as the title suggests, is a compendium intended to provide a coherent synthesis of the history of the region, from prehistoric times to the present day. The work brings together the efforts of researchers from Timișoara, Reșița and Arad, it approaches the history of the Banat in a chronological manner and briefly analyses and explains each significant historical fact, event or process. The work is structured into nine chronological sections, except for the first and last two sections, which deal with the natural setting, Banat figures and chronological milestones in the history of the region. The first section, The Natural Setting, authored by Petru Urdea, presents the relief, climate, hydrography and vegetation of Banat, and anticipates the impression the reader will most likely have by the end – namely, that Banat is a distinctive region.